Analytical Methods for the Determination of Neuroactive Steroids - Kaleta, Michal; Oklestkova, Jana; Novák, Ondřej; Strnad, Miroslav (Biomolecules, 2021)
Neuroactive steroids are a family of all steroid-based compounds, of both natural and synthetic origin, which can affect the nervous system functions. Their biosynthesis occurs directly in the nervous system (so-called neurosteroids) or in peripheral endocrine tissues (hormonal steroids). Steroid hormone levels may fluctuate due to physiological changes during life and various pathological conditions affecting individuals. A deeper understanding of neuroactive steroids' production, in addition to reliable monitoring of their levels in various biological matrices, may be useful in the prevention, diagnosis, monitoring, and treatment of some neurodegenerative and psychiatric diseases. The aim of this review is to highlight the most relevant methods currently available for analysis of neuroactive steroids, with an emphasis on immunoanalytical methods and gas, or liquid chromatography combined with mass spectrometry.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Animals; Immunoassay; lidé; hormony; neurosteroidy; zvířata; Hormones; Neurosteroids; Blood Chemical Analysis; imunoanalýza; biochemická analýza krve; Humans